Question
The functions \( f \) and \( g \) are defined as follows. \[ f(x)=3 x+2 \quad g(x)=-3 x^{2}-2 \] Find \( f(-3) \) and \( g(3) \) Simplify your answers as much as possible.
Ask by Long Reyes. in the United States
Feb 05,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( f(-3) = -7 \) and \( g(3) = -29 \).
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Bonus Knowledge
To find \( f(-3) \), we substitute \(-3\) into the function \( f(x) \): \[ f(-3) = 3(-3) + 2 = -9 + 2 = -7 \] Next, to find \( g(3) \), we substitute \(3\) into the function \( g(x) \): \[ g(3) = -3(3^2) - 2 = -3(9) - 2 = -27 - 2 = -29 \] So, the answers are: \[ f(-3) = -7 \quad \text{and} \quad g(3) = -29 \]